Ziyuglycoside I promotes wound healing via GPR34-mediated activation of group 3 innate lymphoid cells - Kewei Wang; Qingya Sun; Gang Wang; Jiayan Zhang; Yehuang Wang; Bin Jiang; Yang Zhang (Chinese Medicine, 2026)
Abstract Background Sanguisorba officinalis L., a traditional Chinese medicine, has been frequently utilized to promote the healing of burns and scalds. Ziyuglycoside I (ZG-I), a bioactive compound isolated from the roots of S. officinalis L., exhibits significant properties for wrinkle care, antioxidant activity, and antiviral effects. This study aims to explore the underlying mechanisms by which ZG-I promotes wound healing. Methods The efficacy of the treatment was evaluated by monitoring wound closure rates and conducting histological analyses to assess inflammation and re-epithelialization. Immunohistochemistry, utilizing Ki67, α-SMA, and Vimentin antibodies, further characterized the epidermal and dermal repair processes. In vitro, Group 3 innate lymphoid cells (ILC3s) were co-cultured with primary mouse skin fibroblasts, and their proliferation and migration were assessed. The expression of GPR34, secretion of IL-22, and downstream pathways were evaluated. The mechanism was confirmed by knocking down GPR34 in ILC3s. Finally, molecular docking studies, CETSA, and MST experiments validated the interaction between ZG-I and GPR34. Results ZG-I significantly accelerated wound closure in vivo, accompanied by reduced inflammation and immune cell infiltration, enhanced re-epithelialization, and improved collagen fiber organization. Mechanistically, ZG-I upregulated the expression of GPR34 in ILC3s within the wound tissues and elevated the secretion of IL-22. Furthermore, ZG-I dose-dependently enhanced fibroblast viability, proliferation, and migration, while promoting GPR34 and IL-22 expression in ILC3s in vitro. The knockdown of GPR34 in ILC3s reversed these effects and inhibited downstream signaling pathways, including STAT3, AKT, and MAPK. These results establish that ZG-I promotes wound healing by activating GPR34 in ILC3s, which triggers the AKT and MAPK pathways to enhance STAT3 phosphorylation and IL-22 production. Conclusion Our results indicate that ZG-I has the activity of promoting wound healing, and GPR34 can serve as a therapeutic target for ZG-I in the treatment of skin injury-related diseases.